1999
DOI: 10.1088/0954-898x_10_4_304
|View full text |Cite
|
Sign up to set email alerts
|

Natural scene statistics at the centre of gaze

Abstract: Early stages of visual processing may exploit the characteristic structure of natural visual stimuli. This structure may differ from the intrinsic structure of natural scenes, because sampling of the environment is an active process. For example, humans move their eyes several times a second when looking at a scene. The portions of a scene that fall on the fovea are sampled at high spatial resolution, and receive a disproportionate fraction of cortical processing. We recorded the eye positions of human subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
145
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(165 citation statements)
references
References 34 publications
14
145
3
Order By: Relevance
“…Previous studies on human eye movement (Reinagel and Zador 1999) demonstrated a higher contrast at the fixation points compared with randomly chosen parts of static pictures. Therefore, one might expect a higher contrast at the positions that the cats are looking at.…”
Section: Contrast At the Fixation Spotmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies on human eye movement (Reinagel and Zador 1999) demonstrated a higher contrast at the fixation points compared with randomly chosen parts of static pictures. Therefore, one might expect a higher contrast at the positions that the cats are looking at.…”
Section: Contrast At the Fixation Spotmentioning
confidence: 90%
“…A recent study reports a 20% higher contrast at fixation points selected by humans scanning still images (Reinagel and Zador 1999). Hence we compare the contrast at the center of the image, which is the direction the cat preferentially looks at (Guitton et al 1984), with the contrast at higher eccentricities (Fig.…”
Section: Contrast At the Fixation Spotmentioning
confidence: 99%
“…Even though the observed correlation between salience and overt visual selection behavior has been confirmed in multiple studies (e.g., Baddeley & Tatler, 2006;Foulsham & Underwood, 2008;Masciocchi et al, 2009;Parkhurst & Niebur, 2003, 2004Peters et al, 2005;Reinagel & Zador, 1999;Tatler, Baddeley, & Gilchrist, 2005), the answer to the question as to what causes fixations to be predominantly directed toward salient locations still remains unsettled. Showing a correlation between salience and visual selection behavior does not necessarily imply that salience determines visual selection behavior.…”
Section: Eye Movement Control Depends On Visual Contextmentioning
confidence: 99%
“…The work by Reinagel and Zador (1999), for example, shows how subjects look at loci that have high spatial contrast and poor pair-wise pixel correlation, a definition of internal intensity non-uniformity. Edge-density conspicuity is significantly correlated to eye movements loci by Mannan et al (1996).…”
Section: Introductionmentioning
confidence: 99%